Efek Sambaran Petir Terhadap Beda Potensial untuk Sistem Pentanahan Interkoneksi Gardu Induk 150kV - Riza Arif Pratama; Hermawan; Mochammad Facta (Jurusan Teknik Elektro Universitas Andalas, 2022)
The grounding system design of the 150 kV substation have resolve affect in lightning strike area. The purpose of this study is to determine the duration of the potential difference penetration that occurs due to direct or indirect lightning strikes. The parameter method grounding system uses a combination of R and L for the grid section and a combination of RLC for the rod section. Simulations due to direct lightning strikes in nearby areas greatly affect the spike in the amount of potential difference. The potential difference in the area closest to the lightning strike with a maximum surge of 57.42 V with a neutralization duration of 0.21 μs. At the furthest distance from a lightning strike, the maximum potential difference spike is only 3.14 V with a neutralization duration of 2 μs. The average duration of neutralization due to lightning strikes is 2 μs. In the simulation of a direct lightning strike striking electrical equipment, it causes a very high potential difference spike in lightning strike area of ​​992.96 V with a spike duration of 0.012 μs. The farthest area point at the location of the lightning strike has a spike of 31.07 V with a spike duration of 0.06 μs. The duration of neutralization at a potential difference below 1 V, has a duration of more than 2 μs depending on the distance from the location of lightning strike. The grounding system design is able to perform good performance with a fast potential difference neutralization duration in the event of a direct or indirect lightning strike. Lightning strikes that occur will not cause dangerous step and touch voltages for personnel in the 150 kV substation area.